Manuel Estrada Cabrera - Rendón, C; Rendón, Mary Catherine (1988)
﻿ This study offers an account of the presidency of Manuel Estrada Cabrera (1898-1920), concentrating on the political, social and economic aspects of his regime. Following the 'Liberal' inheritance of the Justo Rufino Barrios years (1871-1885), Cabrera is a significant figure in the trajectory of autocratic regimes in Guatemala, which, with few interruptions, stretches from Rafael Carrera (1844-1861) to the present day. Cabrera inherited some of the techniques of Guatemalan dictatorship, but he was also an unorthodox and controversial ruler, remarkable for his sustained retention of power and for the methods he used. The historiography of nineteenth and twentieth-century Guatemala is not generally rich and the Cabrera period is one which has been neglected. Although the United States' and several other diplomatic archives were examined in order to complete this study, it must be stressed that it does not try to explain Guatemalan history through U.S. foreign policy; rather it seeks to focus on the man, and the people who kept him in power for twenty-two years. Diplomats and travellers wrote informative reports which often give frank assessments of character and motive, as well as commenting on internal and external matters in reports which supplement local sources. Secondary sources have also been examined, as well as what remains of Cabrera's private archives, contemporary letters and documents. Furthermore, oral sources added much information. This dictatorship is intrinsically interesting, given the peculiarities and unusual transformations which Cabrera instituted in his government and in national life so as to retain power. This study of Cabrera hopes to enable the reader to appreciate better how such autocracies have propagated themselves in Guatemala and what strains and pressures they were under, and may even afford some pointers for more recent times.